Histological and Histochemical Studies on the Effect of Single Dose of Cyclophosphamide on Migration of Primordial Germ Cells of Fetal Charles Foster Rat – A Preliminary Study - Ray, Biswabina; Potu, Bhagath Kumar (Fırat University, 2007)
Objectives: Effect of single dose Cyclophosphamide (CP), a known teratogen on early ovarian development was studied to understand whether it affects the primordial germ cells (PGC) in migratory phase. Materials and Methods: Adult female pregnant Charles foster rats were divided into control and experimental groups. Experimental group was given intraperitoneal injection of CP at a dose of 2mg/kg of body weight on day 10 of gestation when PGCs were in migratory phase. 12 fetuses from each group were sacrificed on 16th day of gestation to process for histochemical studies (alkaline phosphatase staining), whereas the ovaries of 12 fetuses from each group were collected on 20th day of gestation for histological studies (haematoxyline and eosin staining). Results: Examination of sections of the fetuses of group I showed clusters of large circular PGCs showing blackish brown color in 16 day old fetus. In experimental group, only homogeneous light brown cells were present. Ovaries of 20 day old fetus showed ovarian follicles with large germ cells in the centre in controls. Germ cells were totally absent in treated group. Conclusion: It was concluded that the CP, inhibited migration of PGCs to gonadal ridge leading to absence in ovary. ©2007, Fırat University, Medical Faculty

Amaç: Erken ovaryan gelişimin üzerinde teratojen olduğu bilinen siklofosfamitin (CP), tek dozunun primordial germ hücrelerinin (PGC) migrasyon fazını etkileyip etkilemediği çalışıldı. Gereç ve Yöntem: Yetişkin gebe Charles foster sıçanları kontrol ve deney grubu olmak üzere iki gruba ayrıldı. Deney grubundaki hayvanlara, PGC'nin migrasyon fazında olduğu gestasyonun 10. gününde 2 mg/kg dozunda CP intraperitoneal olarak yapıldı. Her gruba ait 12 fetus gebeliğin 16. gününde histokimyasal çalışmalar (alkalin fosfataz boyama) için çıkarılırken, her gruba ait 12 fetüsün ovaryumları da gebeliğin 20. gününde histolojik çalışmalar (hematoksilen-eosin boyama) için toplandı. Bulgular: Grup I'e ait fetüslerin kesitlerinde geniş sirküler PGC kümeleri, 16 günlük fetüste siyahımsı kahverengi olarak göründü. Deney grubunda ise homojen açık kahverengi hücreler vardı. Kontrol grubuna ait 20 günlük fetüslerin overlerinde, merkezinde geniş germ hücrelerinin olduğu ovaryan foliküller gözlendi. Deney grubunda ise germ hücreleri tamamen yoktu. Sonuç: Siklofosfamit uygulaması primordial germ hücrelerinin gonadal kabartıya göçlerini inhibe etmekte ve overler içinde germ hücrelerinin olmamasına neden olmaktadır. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Fetal Charles foster sıçanların primordial germ hücrelerinin migrayonu üzerine tek doz siklofosfamit'in etkilerinin histolojik ve histokimyasal olarak incelenmesi: Bir ön çalışma